2020
DOI: 10.1101/2020.09.04.282780
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

SARS-CoV-2 infection paralyzes cytotoxic and metabolic functions of the immune cells

Abstract: The SARS-CoV-2 virus is the causative agent of the global COVID-19 infectious disease outbreak, which can lead to acute respiratory distress syndrome (ARDS). However, it is still unclear how the virus interferes with immune cell and metabolic functions in the human body. In this study, we investigated the immune response in 10 acute or convalescent COVID19 patients. We characterized the peripheral blood mononuclear cells (PBMCs) using flow cytometry and found that CD8+ T cells were significantly subsided in mo… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 77 publications
1
4
0
Order By: Relevance
“…Our data are also in agreement with this finding. We showed that delta/omicron infection led to reduced proportions of T lymphocytes and monocytes as original Wuhan strain did to our immune response and this is supported by previously published findings 25,26 . Recent studies highlighted those infections reduced T cell reactivity and led to less neutralizing antibodies against B.1.1.529 (omicron) in naïve infected individuals, whereas in case of triple vaccinated individuals’ magnitude of T cell response was reduced 24 .…”
Section: Discussionsupporting
confidence: 90%
“…Our data are also in agreement with this finding. We showed that delta/omicron infection led to reduced proportions of T lymphocytes and monocytes as original Wuhan strain did to our immune response and this is supported by previously published findings 25,26 . Recent studies highlighted those infections reduced T cell reactivity and led to less neutralizing antibodies against B.1.1.529 (omicron) in naïve infected individuals, whereas in case of triple vaccinated individuals’ magnitude of T cell response was reduced 24 .…”
Section: Discussionsupporting
confidence: 90%
“…Previously, we and others have shown that NK cell and CD8 + T cells were decreased in moderate and recovered COVID-19 patients respectively (Maucourant et al , 2020; Singh et al , 2021; Tian et al , 2021) and both cell types decreased with increased severity of the disease. MAIT cells were also involved in COVID-19 infection (Chen et al ., 2021b).…”
Section: Resultsmentioning
confidence: 63%
“…Serum isolation via centrifugation will be conducted immediately after collection. Human Peripheral Blood Mononuclear Cell (PBMCs) were isolated by the standard Ficoll method (Singh et al ., 2021).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Numbers of circulating dentritic cells ( 10 , 29 , 30 ) and eosinophils ( 31 ) were likewise reduced. Functionally, helper and cytolytic T cells as well as natural killer (NK) cells appeared exhausted ( 19 , 32 ), and the relative fraction of naïve helper T cells was increased at the expense of memory helper T cells ( 11 ). In cultured peripheral blood mononuclear cells (PBMCs) from critically ill COVID-19 patients, anti-CD3/anti-CD28 antibody stimulated IFN-γ production in lymphocytes and endotoxin stimulated TNF-α production in myeloid cells were reduced at least by half.…”
Section: Characteristics Of the Immune Response To Sars-cov-2mentioning
confidence: 99%